Short Communication: Coral reefs condition in Aceh Barat, Indonesia - RUESMA AZHADIN ANNAS; ZAINAL A. MUCHLISIN; MUHAMMAD A. SARONG (Society for Indonesian Biodiversity, 2017)
Annas RA, Muchlisin ZA, Sarong MA. 2017. Short Communication: Coral reefs condition in Aceh Barat, Indonesia. Biodiversitas 18: 514-519. The objective of the present study was to assess the condition of the coral reef ecosystems in the western region of Aceh Province. The study was conducted from September to November 2015 in two locations: Johan Pahlawan and Samatiga Subdistricts, and every location has two sampling sites. The Point Intercept Transect (PIT) method was used in this study. A total of two transects were used at 4-meter and 8-meter depth, respectively. The measured parameters were the percentage of live and dead coral covers, the number of genera, growth forms, species diversity, and dominance indices. Live corals were only found in Lhok Bubon, Samatiga Subdistrict, at 4-meter depth with a coral cover of 17.61%, and no corals were found at 8 meters. In addition, no live corals were also detected in Suak Indrapuri, Johan Pahlawan Subdistrict, at both 4-and 8-meter depth. There were five genera recorded in Lhok Bubon: Favites at 3.77% cover, Montastraea at 1.89% cover, and Montipora and Porites with coral covers of 8.18 and 3.14%, respectively. The diversity and dominance indices of live corals in Lhok Bubon were 1.94 and 0.45, respectively, indicating a low degree of diversity and predominant of Montipora. It is concluded that coral reefs condition in Aceh Barat was categorized as a severely damaged condition.